2012
DOI: 10.1590/s0102-86502012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of estrogen deficiency and tibolone therapy on trabecular and cortical bone evaluated by computed radiography system in rats

Abstract: PURPOSE: To verify the effects of tibolone administration on trabecular and cortical bone of ovariectomized female rats by computed radiography system (CRS). METHODS: The experiment was performed on two groups of rats previously ovariectomized, one received tibolone (OVX+T) while the other did not (OVX), those groups were compared to a control group (C) not ovariectomized. Tibolone administration (1mg/day) began thirty days after the ovariectomy and the treatment remained for five months. At last, the animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(38 reference statements)
0
2
0
1
Order By: Relevance
“…Previous studies investigating the effects of ovariectomy on the stiffness of the bone material of rat cortical bone have reported inconsistent results. Some studies found decreased stiffness (Peng et al, 1997), while others found no change (Miyagawa et al, 2011) or even increased bone material stiffness following ovariectomy (De Carvalho et al, 2012). Other studies found a site specific or time-dependent effect, with initially superior mechanical properties of cortical bone in control rats, which disappears with time (12-28 weeks post OVH) (Peng et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigating the effects of ovariectomy on the stiffness of the bone material of rat cortical bone have reported inconsistent results. Some studies found decreased stiffness (Peng et al, 1997), while others found no change (Miyagawa et al, 2011) or even increased bone material stiffness following ovariectomy (De Carvalho et al, 2012). Other studies found a site specific or time-dependent effect, with initially superior mechanical properties of cortical bone in control rats, which disappears with time (12-28 weeks post OVH) (Peng et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless the majority of studies of osteoporosis are conducted on cancellous (trabecular) bone, while there are fewer studies investigating cortical bone. Furthermore, previous studies examining the effects of ovariectomy on cortical bone in rats reported conflicting results (De Carvalho et al, 2012;Miyagawa et al, 2011;Peng et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…Outra recomendação, parte da terapia hormonal, é o uso de tibolona, um hormônio sintético que apresenta atividade estrogênica, progestagênica e androgênica. Vários ensaios clínicos tem demonstrado que a tibolona mantém a integridade dos ossos e previne perda de massa óssea em mulheres na pós menopausa (168,169). Quatro GPC mencionam o uso de tibolona, sendo que o GPC da Malásia 2012e o GPC de Taiwan (2011) mencionam a ressalva de que o uso de tibolona pode aumentar a incidência de derrame em mulheres acima de 60 anos (59,122).…”
Section: Osteoartriteunclassified